1990
DOI: 10.1046/j.1468-2982.1990.1004177.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Rhythm in Classical Migraine (Migraine with Aura): Abnormalities in the Headache-Free Interval

Abstract: The alpha rhythm of 18 patients with classical migraine (migraine with aura) was studied by EEG spectrum analysis for evidence of neural abnormalities during the asymptomatic period. The temporal relationship of the findings to attacks was studied by serial records in 11 cases. Increased frequency dispersion and frequency asymmetries of the alpha rhythm were found. The records were, however, mostly normal when separated from attacks by at least 10 asymptomatic days. The abnormalities increased significantly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 14 publications
5
31
1
Order By: Relevance
“…The mild abnormality of the posterior (parieto-occipital) alpha rhythm reported by prior authors (Jonkman and Lelieveld 1981;Fachetti et al 1990;Nyrke et al 1990;Neufeld et al 1991;Drake et al 1988;Vonderheid-Guth et al 2000) was essentially confirmed in this study. Spectral analysis and LORETA confirmed the selective involvement of the alpha band and localized the generators of increased alpha activity in the right posterior region of the cortex.…”
Section: Increased Posterior Alpha Activitysupporting
confidence: 89%
See 3 more Smart Citations
“…The mild abnormality of the posterior (parieto-occipital) alpha rhythm reported by prior authors (Jonkman and Lelieveld 1981;Fachetti et al 1990;Nyrke et al 1990;Neufeld et al 1991;Drake et al 1988;Vonderheid-Guth et al 2000) was essentially confirmed in this study. Spectral analysis and LORETA confirmed the selective involvement of the alpha band and localized the generators of increased alpha activity in the right posterior region of the cortex.…”
Section: Increased Posterior Alpha Activitysupporting
confidence: 89%
“…Spectral analysis and LORETA confirmed the selective involvement of the alpha band and localized the generators of increased alpha activity in the right posterior region of the cortex. We confirmed that the occipital alpha abnormality is the most characteristic QEEG abnormality in migraine (Jonkman and Lelieveld 1981;Fachetti et al 1990;Nyrke et al 1990;Neufeld et al 1991;Drake et al 1988). One remaining question is the unilateral or bilateral distribution of the abnormality, an issue that has not been answered by the quoted authors.…”
Section: Increased Posterior Alpha Activitysupporting
confidence: 73%
See 2 more Smart Citations
“…In this regard, Nyrke et al [11] carried out several EEG recordings at different time intervals relative to the crises and found an increase in bioelectrical abnormalities mostly concerning the alpha band in the period immediately preceding the attacks compared to 10 days before.…”
Section: Eeg Mapping During Migraine Attacksmentioning
confidence: 99%